PENYULUHAN KESEHATAN DAN PEMERIKSAAN FISIK, TEKANAN DARAH, GULA DARAH, DAN ASAM URAT DI PUSKESMAS TIGA RUNGGU - Dian Permata Nasution; Marolop Parlindungan Napitu; Jumadiah Wardati (Nusantara Hasana Journal, 2022)
Health education is a strategic effort to raise public awareness of the importance of disease prevention and early detection. This community service report presents health education activities conducted at the Tiga Rungu Community Health Center. These activities included education on healthy lifestyles, blood pressure, blood sugar, and uric acid level checks, and demonstrations of disease prevention measures. These activities were designed to reach various levels of society, especially those with limited access to health information. The implementation method, which included interactive education, live demonstrations, and physical examinations, was conducted in several structured sessions. Several health workers measured and recorded participant data to determine the prevalence of non-communicable diseases in the area. The results of the activity showed a fairly high level of participation, with the majority of respondents benefiting from both knowledge and health checks. Preliminary findings indicate an increase in public awareness and understanding of the importance of routine health checks and adopting a healthy lifestyle. Overall, this activity succeeded in creating constructive interactions between health workers and the community and provided recommendations for further education with a more integrated approach. The findings and recommendations obtained are expected to serve as the basis for preventive efforts in disease prevention and community empowerment at the local level. This report also serves as a reference for related parties in developing sustainable health education programs in the future.